Diffuse Large B Cell Lymphoma Mimicking Granulomatosis with Polyangiitis. (18th May 2016) - Naffaa, Mohammad E.; Rozin, Alexander P.; Horowitz, Netanel; Ben-Itzhak, Ofer; Braun-Moscovici, Yolanda; Balbir-Gurman, Alexandra
Abstract : In a patient with systemic multiorgan disease with overlapping features, the differential diagnosis included infectious diseases, malignancies, and systemic autoimmune or inflammatory diseases. We present an unusual case of a young male with B cell lymphoma who presented with symptoms mimicking systemic vasculitis and review the existing literature.